2022
DOI: 10.1519/jsc.0000000000004372
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kinetic and Kinematic Responses to Rest Redistribution With Heavier Loads in Resistance-Trained Men

Abstract: Chae, S, Bailey, CA, Hill, DW, McMullen, SM, Moses, SA, and Vingren, JL. Acute kinetic and kinematic responses to rest redistribution with heavier loads in resistance-trained men. J Strength Cond Res 37(5): 987-993, 2023-The purpose of this study was to examine mechanical responses to rest redistribution with heavier loads (RR + L) in resistance-trained men. Eight men (23.0 6 4.8 years, 1.76 6 0.06 m, 78.5 6 8.6 kg, back squat [BS] one-repetition maximum [1RM] of 138.7 6 27.9 kg) completed 2 BS exercise sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 37 publications
2
9
4
Order By: Relevance
“…In the previous studies, RR attenuated various acute fatigue indices (e.g., BL, RPE, HR, and percent decline in velocity and power responses) when compared with TS (1,13,14,27,28,33). In this study including the companion article (3), all above-mentioned fatigue indices were not significantly different with trivial ( g = 0.0–0.2) to small ( g = 0.2–0.6) effect size estimates. The equivocal findings of various fatigue responses between previous research (1,13,14,27,28,33) and this study are likely because of the addition of 5% BS 1RM (and approximately 7% of greater volume load).…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…In the previous studies, RR attenuated various acute fatigue indices (e.g., BL, RPE, HR, and percent decline in velocity and power responses) when compared with TS (1,13,14,27,28,33). In this study including the companion article (3), all above-mentioned fatigue indices were not significantly different with trivial ( g = 0.0–0.2) to small ( g = 0.2–0.6) effect size estimates. The equivocal findings of various fatigue responses between previous research (1,13,14,27,28,33) and this study are likely because of the addition of 5% BS 1RM (and approximately 7% of greater volume load).…”
Section: Discussioncontrasting
confidence: 48%
“…In conclusion, this study expands on acute kinetic and kinematic responses reported in the companion article (3) by elucidating acute physiological and perceptual responses. Apart from the percent decline and maintenance in velocity and power (3), other fatigue indices such as BL, RPE, and HR did not significantly differ between RR + L and TS with the small ( g = −0.22), trivial ( g = 0.14), and trivial ( g = −0.08) effects, respectively, when all time points and sets are averaged. Thus, it may be suggested that the manipulation of set structures attenuates these fatigue responses because RR + L completed greater volume load (approximately 7%).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations